Effects of precipitation changes and land-use alteration on streamflow: A comparative analysis from two adjacent catchments in the Qilian Mountains, arid northwestern China - Bai, Xuelian; Zhao, Wenzhi; Liu, Hu; Zhang, Yongyong; Yang, Qiyue; Liu, Jintao; Chang, Xueli (Frontiers in Environmental Science, 2023)
Comparative analysis of the impacts of precipitation and land use on streamflow from adjacent catchments is critical to exploring pathways toward water security and sustainable development. In this work, two adjacent catchments (the Mayinghe and Xidahe, abbreviated as MYC and XDC, respectively) in northwestern China were selected to compare the impacts of precipitation change and land use alteration on streamflow change during 1956–2019 using field observation streamflow data and satellite data. An opposite trend of streamflow was found for the two catchments from 1956 to 2019: the streamflow decreased significantly in the MYC (-0.63 × 107m3/10a, p < 0.05), while it increased in the XDC (0.71 × 107m3/10a, p < 0.05). Land conversion dominated the streamflow reduction in the MYC, with a contribution of about 68.3%. In the XDC, precipitation was confirmed to be the major factor driving the increase in streamflow. The streamflow for farmland irrigation reached 27.97 × 104 m3/km2 in the MYC, which was the leading factor of streamflow reduction in the basin. The findings obtained from this work can shed light on the quantitative understanding of streamflow changes in small catchments and offer a scientific basis for sustainable water management in other inland river basins.